Interaction between low dietary potassium and high dietary sodium intake on blood pressure in adult rats - Mokotedi, Lebogang, Palesa (My University, 2016)
Although it is well known that an increase in sodium intake (Na+) increases BP and is involved in the development of salt-sensitive hypertension (SS-HTN), the mechanism responsible for this increase in BP is uncertain. Further while low dietary potassium (K+) is also associated with the development of SS-HTN it is uncertain to what extent dietary potassium (K+) affects Na+-induced increases in BP. The purpose of this study was to determine whether Na+-induced increases in BP and target organ changes are altered by reductions in K+ intake. Four-month-old male Sprague-Dawley (SO) rats were randomly assigned to three dietary intervention groups for six weeks: a normal Na+ (0.3%), normal K+ (1.6%) group (CON, n=12), a high Na+ (6%), normal K+ (1.6%) group (NK+-HNa+, n=12) and a high Na+ (6%), low K+ (0.01%) group (LK+-HNa+, n=12). Tail-cuff BP, body weight, food and water intake were measured weekly. At termination, urine parameters, right kidney weight as well as left ventricular dimensions and function were measured. Vascular reactivity of the mesenteric and renal arteries was also assessed using a wire-myograph. During the diet intervention, water intake was significantly higher in the NK+-HNa+ and LK+-HNa+ groups compared to the CON group (P<0.0001). Although food intake was significantly lower in the NK+-HNa+ and LK+-HNa+ groups compared to the CON group during the first week (P=0.03 and P=0.05 respectively), no significant differences in body weight were observed between the groups (P>0.05). The urinary Na+/K+ ratio was higher in the LK+ HNa+ compared to the CON and NK+ -HNa+ groups (P<0.001). Following the 6 week dietary intervention, the systolic BP was significantly higher in the NK+-HNa+ and the LK+-HNa+ groups compared to the CON group (P=0.05 and P=0.04 respectively). The diastolic BP was significantly higher in the NK+-HNa+ and LK+-HNa+ groups compared to the CON group (P=O.05 and P=O.02, respectively). The increase in BP was not different between the NK+-HNa+ and LK+-HNa+ groups (P>O.05). In the mesenteric arteries, there was a significant increase in vascular responsiveness to phenylephrine in the NK+-HNa+ group compared to the CON group (P=O.02). However the vascular responsiveness to phenylephrine in the mesenteric arteries was similar between the NK+-HNa+ and LK+-HNa+ groups (P=O.82). No significant differences in vascular reactivity were observed in the renal arteries between the three groups. No significant differences were observed in the left ventricular dimensions and function between the different diet groups (P>O.05). In conclusion, 6 weeks of high Na+ intake increases BP, induces greater phenylephrine-induced contractions in mesenteric arteries but does not affect heart dimensions and function. The greater phenylephrine-induced contractions with a high Na+ intake may be responsible for the increase in BP. However a reduction in dietary K+ intake does not have any effect on the high Na+-induced changes in BP or mesenteric artery reactivity.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Medicine, 2016
Keywords: Sodium intake; Blood pressure; Low dietary potassium; High dietary sodium; Adult rats